La Gouvernance portuaire, un enjeu de développement en Baltique orientale - Arnaud Serry; Lilian Loubet (M@ppemonde)
Over the past two decades, the Baltic sea has known multiple upheaveals, both political and economic. They have notably forced ports to change and adapt to the evolving maritime industries. The ports of the Eastern Baltic have gone from a complementary position as instruments of Soviet collectivism to becoming integrated within a global maritime and portuary system that is synonymous with liberalism. In addition, the issue of modifying governance and portuary regulations, within a rapidly evolving area, is of particular interest to the Baltic space. A literature review and a fieldwork based on two dozen interviews (with elected officials, representatives of port authorities, directors of dock handling companies, heads of chambers of commerce, lobbyists…) highlights how the choices of actors structure ports and affect territorial development (ports, urban areas, inland).